2023
DOI: 10.1002/adma.202307150
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Single‐Atom Catalysis

Giovanni Di Liberto,
Gianfranco Pacchioni

Abstract: Electronic structure calculations represent an essential complement of experiments to characterize single‐atom catalysts (SACs), consisting of isolated metal atoms stabilized on a support, but also to predict new catalysts. However, simulating SACs with quantum chemistry approaches is not as simple as often assumed. In this work, the essential factors that characterize a reliable simulation of SACs activity are examined. The Perspective focuses on the importance of precise atomistic characterization of the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 216 publications
0
8
0
Order By: Relevance
“…11−13 Due to the highly complex structures of these amorphous carbon materials, density functional theory (DFT) is a crucial tool for extracting atomic-level insights on the single atom sites. 14 While the specific coordination can vary across different materials, there is a general consensus that the natureinspired MN 4 sites are responsible for the observed electrochemical activities. 7 For the modeling of the MN 4 sites, most studies assume the pyridinic MN 4 coordination embedded in a graphene-like lattice.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…11−13 Due to the highly complex structures of these amorphous carbon materials, density functional theory (DFT) is a crucial tool for extracting atomic-level insights on the single atom sites. 14 While the specific coordination can vary across different materials, there is a general consensus that the natureinspired MN 4 sites are responsible for the observed electrochemical activities. 7 For the modeling of the MN 4 sites, most studies assume the pyridinic MN 4 coordination embedded in a graphene-like lattice.…”
Section: ■ Introductionmentioning
confidence: 99%
“…32 Unfortunately, as pointed out by Di Liberto et al, this nontrivial source of error is frequently ignored or mishandled, possibly leading to exaggerated results with regard to innersphere reactivity. 14,28 For periodic calculations where hybrid functionals are less practical due to computational costs, the Hubbard correction (DFT + U) could be invoked to mitigate the self-interaction error through calibration with an intuitively "similar" reference material, but it can still cause issues pertaining the transferability of Hubbard parameters and reproducibility across systems. 28 In the same publication, it was also reported that even with a reliable GGA + U that matched the results from hybrid functionals, the reactivity on periodic systems can be artifacts of suboptimal lattice parameters, which are not typically optimized during the reaction studies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Catalysis with single metal atoms is a potentially relevant new frontier with an expected impact on the incoming energy and environmental transition. A single-atom catalyst (SAC) is made by a transition metal (TM) atom embedded in a solid matrix. SACs bridge the two worlds of homogeneous and heterogeneous catalysts. The former are often more active but the latter are more stable and for this reason are involved in the vast majority of technological applications of catalysis . Indeed, an SAC is a heterogeneous catalyst with atomic dispersion and a well-defined local environment.…”
Section: Introductionmentioning
confidence: 99%